2008
DOI: 10.1016/j.pmrj.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Contralateral and Ipsilateral Cane Use On Normal Adult Gait

Abstract: Both ipsilateral and contralateral cane use reduced cadence and mean peak vertical plantar force on the limb advanced with the cane in healthy young adults. Double limb support increased with cane use likely due to the reduced cadence and initial unfamiliarity with using an assistive device. A clinical implication of these findings is that prescription of canes for either ipsilateral or contralateral use effectively offloads a designated lower limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Subjects also experienced a 14%‐16% decrease in gait velocity with contralateral or ipsilateral cane use compared with walking without a cane; the lower walking speed was due to a decrease in cadence. Similar results with respect to peak vertical ground reaction force on the assigned limb and cadence have been reported when normal subjects walked with a cane contralateral or ipsilateral to a right or left lower limb that was randomly “assigned” as the reference limb [20].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Subjects also experienced a 14%‐16% decrease in gait velocity with contralateral or ipsilateral cane use compared with walking without a cane; the lower walking speed was due to a decrease in cadence. Similar results with respect to peak vertical ground reaction force on the assigned limb and cadence have been reported when normal subjects walked with a cane contralateral or ipsilateral to a right or left lower limb that was randomly “assigned” as the reference limb [20].…”
Section: Discussionsupporting
confidence: 76%
“…These investigators also indicated that using the contralateral cane so that the tip of the cane touches the ground at the same time as the foot or using the ipsilateral cane so that the tip of the cane touches at the same time as the heel were the optimal techniques to decrease peak vertical reaction force on the foot. Both ipsilateral and contralateral cane use reduced cadence by 13% compared with walking unaided in healthy young adults [20].…”
Section: Introductionmentioning
confidence: 92%
“…A cane reduced peak vertical forces measured using foot pressure sensors [60]. A cane in the contralateral hand resulted in lower shoe forces than one in the ipsilateral hand [61].…”
Section: Therapeutic Modulation Of Knee Forcesmentioning
confidence: 99%
“…This may be attempted through the use of offloading strategies such as assistive devices [26]. A single point cane can decrease vertical loading by 11-25% [27,28]. Total contact casts, patellar tendon bearing braces, and removable walking boots have been shown to offload the foot [29,30].…”
Section: Nonmedicinal Treatment Choices In the Management Of Ankle Osmentioning
confidence: 99%